Stability of cylindrical mesh covering shells in non-linear statement - Siianov, O. I. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper considers the problem of cylindrical mesh covering shell in geometrical non-linear statement. The character of shell deformation with imperfections is investigated , its sensitivity to form imperfections is determined.